Pengaruh Konsep Diri dan Regulasi Diri Terhadap Stres Akademik Pada Mahasiswa - Irfandi Nizar Gumiwang; Fayza Samara Nur Wahidah; Atining Papat Mekanah; Lucky Purwantini (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze the influence of self-concept and self-regulation on academic stress in students of Universitas Islam 45 Bekasi. A quantitative approach with a correlational design was used to test the relationship between these variables. Data were collected through a Likert-based questionnaire on 137 active students aged 18–23 years. The results of the analysis showed that self-concept had a significant negative relationship with academic stress, while self-regulation did not show a significant effect. These findings indicate the importance of self-concept in managing students' academic stress. Although self-regulation was not statistically significant, there was still a relevant negative relationship. The implication of this study is the need for self-concept development programs to support student well-being, while improving self-regulation can be considered in other contexts. This study provides new insights into managing academic stress and supports more effective interventions in higher education settings.